Mating Calls of Certain Philippine Anurans (Microhylidae, Ranidae) - Alcala, Angel C.; Joermann, Gerhard; Brzoska, Josef (Silliman Journal, 2024)
The mating calls of five Philippine anurans are analyzed. Kaloula picta and K. conjuncta, both belonging to the family Microhylidae, have stereotyped and simple-structured mating calls. The calls of these two species differ in temporal parameters. In contrast, three species of the family Ranidae--Rana erythraea, R. Signata and Ooeidozyga laevis--have more complex calis. Those of R. erythraea and Ooeidozyga laevis are very variable, each with-different call types, and that of R. signata contains only one type. The calls of these two erythraea include frequency-modulated tone pips and harmonic elements, while those of the other two ranids have mainly pulsed signals. Mating calls of these Philippine frogs may be used in clarifying taxonomic problems.